2016
DOI: 10.1038/srep36943
|View full text |Cite|
|
Sign up to set email alerts
|

Murine hypothalamic destruction with vascular cell apoptosis subsequent to combined administration of human papilloma virus vaccine and pertussis toxin

Abstract: Vaccination is the most powerful way to prevent human beings from contracting infectious diseases including viruses. In the case of the human papillomavirus (HPV) vaccine, an unexpectedly novel disease entity, HPV vaccination associated neuro-immunopathetic syndrome (HANS), has been reported and remains to be carefully verified. To elucidate the mechanism of HANS, we applied a strategy similar to the active experimental autoimmune encephalitis (EAE) model - one of the most popular animal models used to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Previously, Aratani S et al reported that HPV vaccines induce murine EAE-like disease, suggesting that the HPV vaccine adjuvant is the cause of mouse EAE exacerbation 13 . Although HPV vaccines induce pro-inflammatory cytokine expression as described above, the administration of Gardasil and Cervarix did not affect murine EAE clinical scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Aratani S et al reported that HPV vaccines induce murine EAE-like disease, suggesting that the HPV vaccine adjuvant is the cause of mouse EAE exacerbation 13 . Although HPV vaccines induce pro-inflammatory cytokine expression as described above, the administration of Gardasil and Cervarix did not affect murine EAE clinical scores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is an autoimmune disorder affecting the CNS such as ADEM, and it represents an animal model of multiple sclerosis 12 . There was a report that HPV vaccines induce EAE-like symptoms in mice 13 ; however, the paper was retracted because of an inappropriate experimental approach 14 . Cervarix, an HPV vaccine, contains the AS04 adjuvant, which includes monophosphoryl lipid A (MPLA) and aluminum adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…Further large-scale studies are needed to elucidate the pathogenesis of this unusual phenomenon. To this end, a murine pathological model was recently established by combined administration of HPV vaccine and pertussis toxin [ 40 ], which might be helpful for investigating immune-related pathological conditions in this post-vaccinated disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mice have been reported to have developed autoantibodies after intraperitoenal injection of hydrocarbon oil-based adjuvants (6). In another murine model, concomitant exposure to HPV vaccine and pertussis toxin has reportedly resulted in hypothalamic destruction (7). Similarly, exposure to HBV vaccine has been found to accelerate disease progression in a murine model of lupus (8).…”
Section: Vaccination-induced Autoimmunity: Potential Mechanismsmentioning
confidence: 99%